2018
DOI: 10.6061/clinics/2018/e476s
|View full text |Cite
|
Sign up to set email alerts
|

Improving adenoviral vectors and strategies for prostate cancer gene therapy

Abstract: Gene therapy has been evaluated for the treatment of prostate cancer and includes the application of adenoviral vectors encoding a suicide gene or oncolytic adenoviruses that may be armed with a functional transgene. In parallel, versions of adenoviral vector expressing the p53 gene (Ad-p53) have been tested as treatments for head and neck squamous cell carcinoma and non-small cell lung cancer. Although Ad-p53 gene therapy has yielded some interesting results when applied to prostate cancer, it has not been wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 99 publications
0
9
0
1
Order By: Relevance
“…ER and PR may participate in abnormal proliferation and inhibit normal cell apoptosis. 23 P53 gene abnormality is closely related to the carcinogenesis of cervical epithelial cells. P53 gene mutation exists in cervical squamous intraepithelial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…ER and PR may participate in abnormal proliferation and inhibit normal cell apoptosis. 23 P53 gene abnormality is closely related to the carcinogenesis of cervical epithelial cells. P53 gene mutation exists in cervical squamous intraepithelial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Especially HPV infection is not the only pathogenic factor of cervical squamous intraepithelial lesions. The functional changes of oncogenes and tumor suppressor genes also play a key role in the occurrence and development of cervical squamous intraepithelial of DNA replication and transcription during endometrial cell proliferation, while progesterone has antagonistic effect on estrogen, which can make dysplasia cells mature and down-regulate at the level of transcription and post-transcription [22] . Some studies have shown that ER and PR are most expressed in normal endometrium, but less expressed in cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Gene therapy has brought about a breakthrough for the treatment of prostate cancer, and a number of studies have identified a substantial number of genes that may be potential targets for the treatment of this malignancy (11,12). In the present study, AIPC cell lines PC3 and DU145, which do not respond to androgens, glucocorticoids or epidermal/fibroblast growth factors, were selected as models (13,14).…”
Section: Introductionmentioning
confidence: 99%